2022
DOI: 10.3233/jad-215224
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Gut Microbiota and Alzheimer’s Disease: A Systematic Review

Abstract: Background: In recent years, scientific research on the gut microbiota and their relationship with some diseases, including neurological ones, has notably increased. As a result of these investigations, the so-called gut-brain axis arises. Despite its influence on the evolution and development of cognitive impairment, the gut-brain axis is little defined and demonstrated. Objective: To provide the best scientific evidence available on the relationship between the gut microbiota and Alzheimer’s disease. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…An improved understanding of LPS molecular genetic interactions along the GI tract–CNS axis involving GI-tract-derived microbial neurotoxins, AD and other related disorders should further support the hypothesis of altered LPS–miRNA–mRNA coupled signaling networks, and these concepts are currently supported by recently described experimental-findings in the scientific literature [ 29 , 30 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 53 , 54 , 55 , 56 , 57 ]. For example, targeting and/or modulating GI-tract-microbiome-LPS-mediated, miRNA-30b-regulated NF-L pathways and other miRNA-mediated gene expression circuitry could be valuable in the design of future therapeutic strategies that: (i) could support and maintain cytoarchitectural components essential for neuronal shape, axonal caliber, inter-neuronal signaling and synaptic plasticity; and (ii) may more effectively manage the many neurological diseases in which NF-L gene expression and abundance play a defining and/or determinant role [ 29 , 39 , 55 , 56 , 57 ]. Recent emerging evidence on dietary-based modifications of microbial dysbiosis may also be an attractive means to alter the abundance, speciation and complexity of enterotoxigenic forms of AD-relevant microbes such as B. fragilis and their potential for their long-term pathological discharge of highly neurotoxic microbial-derived glycolipid/lipoglycan secretions such as LPS [ 51 , 52 , 58 , 59 , 60 ] ( Figure 2 ).…”
Section: Lps-mediated Effects On Neurofilament Light (Nf-l) Chain Gen...supporting
confidence: 55%
See 3 more Smart Citations
“…An improved understanding of LPS molecular genetic interactions along the GI tract–CNS axis involving GI-tract-derived microbial neurotoxins, AD and other related disorders should further support the hypothesis of altered LPS–miRNA–mRNA coupled signaling networks, and these concepts are currently supported by recently described experimental-findings in the scientific literature [ 29 , 30 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 53 , 54 , 55 , 56 , 57 ]. For example, targeting and/or modulating GI-tract-microbiome-LPS-mediated, miRNA-30b-regulated NF-L pathways and other miRNA-mediated gene expression circuitry could be valuable in the design of future therapeutic strategies that: (i) could support and maintain cytoarchitectural components essential for neuronal shape, axonal caliber, inter-neuronal signaling and synaptic plasticity; and (ii) may more effectively manage the many neurological diseases in which NF-L gene expression and abundance play a defining and/or determinant role [ 29 , 39 , 55 , 56 , 57 ]. Recent emerging evidence on dietary-based modifications of microbial dysbiosis may also be an attractive means to alter the abundance, speciation and complexity of enterotoxigenic forms of AD-relevant microbes such as B. fragilis and their potential for their long-term pathological discharge of highly neurotoxic microbial-derived glycolipid/lipoglycan secretions such as LPS [ 51 , 52 , 58 , 59 , 60 ] ( Figure 2 ).…”
Section: Lps-mediated Effects On Neurofilament Light (Nf-l) Chain Gen...supporting
confidence: 55%
“…Early studies suggested that the identification and characterization of unique microbial signatures in neuropsychiatric diseases could provide new possibilities in targeted anti- or pro-biotic treatments [ 31 , 32 ]. However, HMP and parallel GI-tract microbiome studies involving multiple human populations and animal models of AD provided evidence indicating that due to wide variation in the microbial and genetic composition of individual GI-tract microbiomes even during healthy aging, it would be difficult to associate the abundance, speciation and/or complexity of any single microbial genus, species or classification with any single human disease [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 45 , 47 , 55 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This is especially relevant to highly complex and heterogeneous neurological syndromes, such as AD, prion disease and other age-related neurodegenerative disorders, against their complex background of familial genetics, patient age, gender, drug history, age of onset and duration, inter-current disease and other critical environmental and lifestyle risk factors [ 61 , 62 , 63 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, recent research results suggest a deep impact of the gut microbiota on brain functions (“gut-brain axis”). For instance, associations of distinct gut microbiota signatures with autism spectrum disorders such as the ADNP syndrome, with Alzheimer's disease, and with other morbidities of the nervous system have been described [ 19–21 ].…”
Section: Introductionmentioning
confidence: 99%